Internship as a Young Professional under the Business Analyst Team of Orange Business Development Ltd. - Abrar Talukder, Md. Galib (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.